Malignant triton tumor of the rectum – A case report and review of the literature - Herzberg, J. (Int J Surg Case Rep, 2020)
INTRODUCTION: Malignant triton tumors (MTT) are rare but highly aggressive tumors that originate from the Schwann cells. These tumors can occur in any part of the body, mostly present late and carry poor prognosis. PRESENTATION OF CASE: We present a 24-year-old man with a rectal MTT causing non-specific abdominal pain and recurring ileus. The MRI showed a rectal mass near the urinary bladder with compression on the seminal vesical. A complete surgical resection of the tumor was performed. The immunohistological report confirmed a rectal MTT. Because of persistent ileus during the post-operative palliative chemotherapy, another tumor debulking was performed. The patient died 9 months after the diagnosis of MTT due to local recurrence under chemotherapy. DISCUSSION AND CONCLUSION: MTTs are uncommon tumors in young age with high morbidity and mortality because of local recurrence also after complete resection.